2000
DOI: 10.4049/jimmunol.165.1.397
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Fractalkine Inhibits Fas-Mediated Cell Death of Brain Microglia

Abstract: Fractalkine is a CX3C-family chemokine, highly and constitutively expressed on the neuronal cell surface, for which a clear CNS physiological function has yet to be determined. Its cognate receptor, CX3CR-1, is constitutively expressed on microglia, the brain-resident macrophages; however, these cells do not express fractalkine. We now show that treatment of microglia with fractalkine maintains cell survival and inhibits Fas ligand-induced cell death in vitro. Biochemical characterization indicates that this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 38 publications
6
128
0
3
Order By: Relevance
“…How CX3CR1 works in the model requires further definition: does it only promote monocyte/macrophage influx from the blood into the wound as the transfer experiments suggest, or does it also mediate macrophage retention in the wound? CX3CL1-CX3CR1 signaling has also been reported to maintain cell survival and inhibit Fas-dependent cell death of brain microglia in vitro (47). Perhaps it also regulates survival of dermal macrophages in wounded skin.…”
Section: Discussionmentioning
confidence: 99%
“…How CX3CR1 works in the model requires further definition: does it only promote monocyte/macrophage influx from the blood into the wound as the transfer experiments suggest, or does it also mediate macrophage retention in the wound? CX3CL1-CX3CR1 signaling has also been reported to maintain cell survival and inhibit Fas-dependent cell death of brain microglia in vitro (47). Perhaps it also regulates survival of dermal macrophages in wounded skin.…”
Section: Discussionmentioning
confidence: 99%
“…Others have previously reported that CX3CL1 provides cell-survival signals on ligation of CX3CR1 50,51 and inhibits Fas-mediated apoptosis in microglial cells. 52 Whether or not the CX3CL1-CX3CR1 pathway promotes cell-survival signals and contributes to the accumulation of alveolar and parenchymal macrophages observed in COPD is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, WT1-induced growth factors which we have identified, such as CX3CL1, IL-11, and FGF-1, may confer mesenchymal cell survival and differentiation through autocrine circuits. CX3CL1/Fractalkine inhibits apoptosis in neurons and microglia (53,54), and IL-11 protects skin from UVB-induced apoptosis (55) and from nephrotoxic serum-induced glomerulonephritis (56). The importance of FGF signaling in kidneys has been demonstrated using a transgenic mouse expressing dominant negative FGF receptor (57).…”
Section: Discussionmentioning
confidence: 99%